BALB/c Mice as Animal Model in Dengue Infection Research: Role of Endothelial Activation - I Made Susila Utama; Tuti Parwati Merati; Made Bakta; Made Jawi (Faculty of Medicine, Universitas Diponegoro, 2023)
Introduction. There were various challenges in using experimental animals model for dengue infection studies aside from the fact that dengue infection only naturally affects humans and does not manifest clinical signs as in humans. Various experimental animals have been used in dengue research, but the mouse model is more widely used since it is easier to obtain although sometimes they do not show clinical symptoms but may still measure the immune response. BALB/c mice are immunocompetent mice that have the potential to be used in dengue infection research. Endothelial cell activation plays a role in the pathogenesis of dengue virus infection which contributes to plasma leakage. One of the biomarkers of endothelial cell activation is soluble intercellular adhesion molecule 1 (sICAM-1).Method. An analytic observational study was conducted using BALB/c mice aged 8 weeks and weighed 40 grams. Selected BALB/c mice were randomly assigned to serotype 2 dengue virus containing 2.1 x 106 pfu/ml intraperitoneally, given only once. A total of 11 mice were injected with dengue virus serotype 2 and 11 mice were not injected with dengue virus. On the second day of virus injection, non structural (NS) 1 antigen dengue examination was carried out to prove that the BALB/c mice were indeed infected with dengue virus. In BALB/c mice that were proven to be infected with dengue virus, sICAM-1 levels were examined in serum after 7 days of infection. Mice that were not injected with dengue virus also examined sICAM-1Results. All of BALB/c mice injected with dengue virus were proven to be infected, as indicated by the detection of NS1 antigen in their serum. The mean serum level of NS1 antigen was 88.35 ng/ml (mean 95.34 ng/ml and standard deviation 21.94). The level of sICAM-1 in BALB/c mice infected with dengue virus (mean = 1.34) was significantly higher than mice that were not infected (mean = Â 0.79), with a p-value 0.045Conclusions. BALB/c mice were proven to be infected with dengue virus by detecting ns1 dengue virus antigen in the serum. The sICAM-1 levels in the group of BALB/c mice infected with dengue serotype 2 were significantly higher than the BALB/c mice that were not infected with dengue virus.